Serum Endocan Level and Its Correlation with Clinicopathologic Features in Patients with Papillary Thyroid Cancer - ŞENER, Musa Kürşad; KARAKÖSE, Melia; KOCABAŞ, Muhammet; KARS, Taha Ulutan; SOLAK, Cihad; YÖNET, Fethi; GEREK, Mehmet Emin; YERLİKAYA, Fatma Hümeyra; KULAKSIZOĞLU, Mustafa; KARAKURT, Feridun (Endocrinology Research and Practice, 2022)
Objective: Endocan, also known as endothelial cell specific molecule- 1, is a vascular endothelium-derived factor and plays a key role in angiogenesis. The aim of this study is to assess serum endocan level in papillary thyroid cancer (PTC) patients which has not been investigated before. Material and Methods: This study included 48 patients with PTC who underwent total thyroidectomy between November 2018 and May 2019. As the control group, 40 age- and sexmatched cases with benign thyroid nodules were included. Serum samples were obtained from the patients before surgery. Serum endocan levels of the patients and controls were measured and the results were compared. The relationship between endocan levels and clinicopathological factors was investigated. Cases with benign thyroid nodules were included as the control group. Results: PTC patients had higher mean serum endocan level than control subjects (45.1±9.6 vs. 37.7±8.3 pg/mL, p<0.001). In PTC patients, there was no relationship between serum endocan levels and histopathologic variant, lymphatic or vascular invasion, surrounding thyroid tissue invasion, lymph node metastasis, surgical margin status, tumor-node-metastasis stage and American Thyroid Association risk stratification group, age and tumor size. Conclusion: This study suggests that, if supported by more comprehensive studies with a sufficiently large sample size in the future, serum endocan level may be used as an adjunctive test in the diagnosis of PTC in patients with thyroid nodules.